Extant Roofing Pattern and Early Decay of Residential Buildings in Port Harcourt Municipality, Rivers State - Esau James Esau; Pepple, Tonye, Dagogo (International Journal of Environmental Planning and Development Architecture, 2025)
The design and construction pattern of roofs in the tropical environment like Port Harcourt Municipality, Rivers State is a major factor that determined how functional and the life span of building components and materials. In recent time residential building components and materials had been observed to decay earlier than expected due the existing roofing pattern. This study is aimed at assessing the extant roofing pattern and identified factors responsible for early decay of residential building in Port Harcourt Municipality. The study adopted mixed-methods research approach using concurrent triangulation design for data collection. The study employed purposive and simple random sampling techniques to select three (3) neighbourhoods (Port Harcourt Township, Oromenike and Mgbundungwu) and respondents for collection of data which a total of 357 respondents were sampled. Structured interview questionnaire and key informant methods were used to collect data from the respondents including building occupants, MDAs and professionals in the built environment. Checklist, physical observation and photograph were also used to characterize roofing patterns in residential buildings of the study area. The following are the findings of the study: the design and construction pattern of roofs ; such as low roof angle (pitch), insufficient eave (overhang), and substandard materials, were the major factors inducing early decay of building components and materials, It was concluded that professionals in the built environment should take into conglenence the tropical climate of the study area as a guild to both the roof type, pitch and choice of materials in the study area The following recommendations are made, roof pattern of residential buildings should factor in the peculiar tropical climate from the design and construction stage, roof angles (pitch) should not be less than 250 and above with an overhang of 900mm and above.
Keywords: Roof; early decay; port harcourt city; residential building; roof pattern